Information on Firm Value Determinants Based on Investment Decision and Dividend Policy - Rahmadi, Zara Tania; Yulianto, Kampono Imam; Damayanty, Prisilia (International Journal of Artificial Intelligence Research, 2023)
Due to the high level of investment that occurs today, this study aims to determine the Determinants of Investment Decisions, Dividend Policy and its Implications for Firm Value. The research method used in this research is quantitative method with the type of data used is panel data (pooled data) which is a combination of data from time series data with cross section data. The population in this study are companies listed on the Jakarta Islamic Index (JII) for the period 2019 to 2021. For sampling techniques in this study using non-random sample techniques with purposive sampling method. To answer the alleged hypothesis in this research using the panel regression model estimation method where the statistical tool that will be used is EViews 10. The output of this research will be published in the Sinta 2 indexed national journal, for the level of technology readiness (TKT) of the proposed research, namely the TKT type of social humanities and education, which is defined in the utilisation of R & D results for the improvement of policies and governance with the achievement of indicator point 3, namely the results / outputs of R & D delivered as a reference and information for related parties